Symbiotic microparticles produced through spray-drying-induced in situ alginate crosslinking for the preservation of Pediococcus pentosaceus viability - Frota, Elionio Galvão; Pessoa, Amanda Romana Santos; Souza de Azevedo, Pamela Oliveira de; Dias, Meriellen; Veríssimo, Nathalia Vieira Porphirio [UNESP]; Zanin, Maria Helena Ambrosio; Tachibana, Leonardo; de Souza Oliveira, Ricardo Pinheiro (Elsevier, 2024)
Probiotic microorganisms are a promising alternative to antibiotics in preventing and treating bacterial infections. Within the probiotic group, the lactic acid bacteria (LAB)stand out for their health benefits and for being recognized as safe by regulatory agencies. However, these microorganisms are sensitive to various environmental conditions, including the acidic environment of the stomach. Faced with these obstacles, this work aimed to promote the symbiotic microencapsulation of LAB in a composite matrix of alginate and prebiotics to enhance their survival and improve their probiotic activity during gastrointestinal transit. We evaluated the effect of inulin, fructo-oligosaccharides (FOS) and mannan-oligosaccharides (MOS) as prebiotic sources on the growth of Pediococcus pentosaceus LBM34 strain, finding that MOS favored LAB growth and maintenance of microencapsulated cell viability. The symbiotic microparticles were produced using the spray-drying technique with an average size of 10 μm, a smooth surface, and a composition that favored the stabilization of live cells according to the FTIR and the thermal analysis of the material. The best formulation was composed of 1 % of alginate, 10 % MOS and 1 % M10 (% w/v), which presented notable increases in the survival rates of the probiotic strain in both alkaline and acidic conditions. Therefore, this industrially scalable approach to symbiotic LAB microencapsulation can facilitate their growth and colonization within the host. This effort aims to contribute to reducing antibiotic reliance and mitigating the emergence of new zoonotic diseases, which pose significant challenges to public health.
Keywords: Bacteriocin; Encapsulation; FOS; Inulin; MOS; Prebiotic; Probiotic